Tumor-infiltrating lymphocyte therapy: therapeutic advances and prospects - Sarker Drishty Badhon; Gonzalez Marian M.; Martinez Sophia; Sang Qing-Xiang Amy (Visualized Cancer Medicine)
Tumor-infiltrating lymphocyte (TIL) therapy has evolved from a pioneering experimental approach to a clinically validated treatment strategy, underscored by the recent approval of lifileucel (Amtagvi) by the Food and Drug Administration (FDA) for advanced melanoma refractory to existing therapies. Initially successful in melanoma due to its high tumor mutational burden (TMB) and immune-reactivity, contemporary efforts extend TIL applications to other solid tumors, including lung, cervical, and colorectal cancers. However, these lower-TMB malignancies typically require the selective enrichment of tumor-specific T cells to achieve significant clinical efficacy. The therapeutic potential of TILs is influenced by critical factors, including cell dose, T-cell phenotype and differentiation state, tumor-specific reactivity, and the ability to persist and expand within patients post-infusion. Emerging techniques, including single-cell transcriptomics and biomarker-guided TIL selection (e.g., CD137, CD103 markers), have provided deeper insights into the characteristics correlating with successful outcomes. Ongoing clinical trials highlight future directions, including genetically engineered TILs with chimeric antigen receptor (CAR) or immune checkpoint knockout, improved cytokine support strategies to enhance T-cell expansion and reduce toxicity, and optimized lymphodepletion regimens. Establishing clear quality attributes for TIL manufacturing will be essential for consistent clinical success, paving the way toward personalized and robust immunotherapeutic approaches across diverse cancer types.